Examining the Role of DNM1L-Dependent Mitochondrial Fission and Mitophagy Receptors During Skeletal Muscle Differentiation - Ma, Andrew (University of Waterloo, 2020)
Mitochondrial fission is necessary for the remodelling of existing mitochondria during skeletal muscle differentiation. When there is a need for muscle regeneration or repair, stem cell-like myoblasts exit the cell cycle, restructure their mitochondrial networks, and fuse together to form multinucleated myotubes. Studies investigating the cellular process of DNM1L (dynamin 1-like)-dependent mitochondrial fission during skeletal muscle differentiation are limited. Here, we demonstrated the effect of DNM1L inhibition with mdivi 1 (mitochondrial division inhibitor-1), a pharmacological inhibitor of DNM1L self-assembly, during murine C2C12 myoblast differentiation. Myoblasts treated with mdivi-1 exhibited a hyperfused mitochondrial network which consisted of increased branch lengths and inversely decreased the number of mitochondrial puncta, suggesting the reduction of DNM1L-driven mitochondrial fission events. Furthermore, inadequate mitochondrial fission suppressed MYH (myosin heavy chain) levels and concomitantly decreased myoblast cell fusion during myotube formation. To further support the notion that DNM1L is required for myoblast differentiation, we attempted to genetically knockdown Dnm1l expression with a short hairpin RNA which marginally decreased DNM1L protein content and dramatically abolished MYH levels. In contrast, DNM1L overexpression in differentiated myoblasts did not impair MYH levels. Moreover, we examined the effect of excess mitochondrial fission with CCCP (carbonyl cyanide 3 chlorophenylhydrazone), a chemical inducer of mitochondrial depolarization, which promoted MAP1LC3B (microtubule associated protein 1 light chain 3 beta) conversion indicating that CCCP stimulated autophagy, an intracellular degradation system for the removal of proteins and organelles. Previous studies demonstrated the importance for the degradation of mitochondria facilitated by the mitophagy receptors BNIP3 (BCL2 interacting protein 3) and PRKN (parkin RBR E3 ubiquitin protein ligase) but overlooked the relation of DNM1L during skeletal muscle differentiation. In this study, we examined the mitophagy-related proteins BNIP3 and PRKN in the context of DNM1L inhibition during myoblast differentiation. Importantly, mdivi-1 treated myoblasts overexpressed with BNIP3 ameliorated myoblast cell fusion and upregulated MYH, whereas PRKN overexpression ineffectively restored myotube formation. Collectively, our findings further support the integral role of DNM1L in the process of mitochondrial fission, as well as emphasize the interplay between DNM1L and mitophagy receptors during C2C12 myoblast differentiation.
Keywords: skeletal muscle differentiation; skeletal muscle regeneration; mitochondrial fission; mitophagy; dynamin 1-like protein